TO GENERATE DATA AT ALL COSTS FOR TRAFFIC CELEBRITIES: THE REMAKING OF CHINESE NEW POOR THROUGH DATA-DRIVEN FAN CULTURE - Hou, Jiaxi (AoIR Selected Papers of Internet Research, 2023)
Among Chinese fans of ‘traffic celebrities’ (liuliang mingxing, 流量明星), to generate excessive data either on digital platforms or in various sales charts so as to inflate certain entertainer’s popularity has become a normalized ritual to demonstrate one’s fan identity. The so-called fandom economy effectively mobilizes fans from diverse socioeconomic backgrounds to consume and participate, thus, generates tremendous revenues. However, when some fans could easily satisfy their consumerist desire for being economically powerful and socially successful, many more—who are seduced by the communitas of fan activism and agency as consumers —are unable or not yet fully prepared to afford this lifestyle. Depending on an eighteen-month ethnography, this study unpacks how these fans are seduced, to some extent included, but still exploited in the transitional Chinese consumer society as new poor (Bauman 2005), where digital platforms become new structuring nexus and transform existing power dynamics.